Exploring and Revitalizing Anhui's Traditional Music: A Cultural Journey - CAO, SHUANG (Pacific International Journal, 2024)
This paper explores the intricate tapestry of Anhui's traditional music culture, situated in the heart of China, where history, geography, and artistic expressions converge. Spanning epochs marked by conflicts and migrations, Anhui's Traditional Music emerges as a resilient testament to the diversity inherent in Chinese musical history. However, the study unveils critical challenges threatening its inheritance and development. Weak awareness, insufficient exploration of cultural resources, and a succession gap demand urgent attention. Addressing these challenges, the paper proposes practical strategies for the revitalization of Anhui's musical heritage. Broadening dissemination paths, innovating traditional music content, strengthening cultural inheritor training, and integrating music culture into schools form a comprehensive framework. Beyond academic discourse, these strategies present a proactive response to ensure the continuity of Anhui's rich cultural legacy. In envisioning the future, the paper emphasizes the integration of modern technologies, calling for a dynamic engagement with dissemination platforms. This is not a static preservation effort; rather, it is a dynamic call to breathe new life into Anhui's Traditional Music. The proposed strategies aim to usher in an era where Anhui's musical traditions resonate vibrantly, transcending temporal boundaries and enriching the cultural mosaic of China. The paper, thus, extends a collective call to action, inviting scholars, enthusiasts, policymakers, and the public to actively participate in this cultural revitalization, ensuring the enduring legacy of Anhui's Traditional Music in the cultural fabric of the nation.